Fast Frequency Response from MMC-HVDC with Varying Dead Band Implementation. Issue 28 (2018) - Fradley, J.; Preece, R.; Barnes, M.
Abstract: Future electrical power systems will have an increased percentage of renewable generation which will reduce the amount of synchronously connected rotating kinetic energy and inertia. With reduced levels of inertia, the system frequency will be prone to a faster rate of deviation from its nominal value. As traditional frequency containment may be too slow under low inertia conditions, it is expected that systems will require renewable sources of generation to provide some additional frequency containment response (FCR) in suitably fast timeframes. Of particular interest in this research is how the use of modular multilevel converter (MMC) based HVDC interconnectors could be operated to provide FCR. To avoid excessive operation of MMC-based FCR, dead bands around nominal frequency are often suggested. Here, the implementation of the dead band is revisited to investigate how different variants of implementations (namely, continuous and discontinuous), could improve frequency response from an MMC. A continuous implementation with a variable controller gain value that is dependent on dead band size is shown to reduce frequency nadir. The discontinuous implementation is shown to reduce frequency nadir further and when modified with latching behavior also improves frequency recovery. This research highlights that alternative dead band implementation for MMCs, particularly a discontinuous dead band with latching behavior could improve frequency response in future power systems.